Analisis Hubungan Antara Opini Auditor dan Kualitas Audit dengan Penjualan Saham Institusional - Isasari Karuniani Gusti; Endang Kiswara (Diponegoro Journal of Accounting, 2012)
This study aims to examine the relation of auditor opinion and audit quality to stocks traded. This study is using ANOVA, which is used for examine the relation of independent variable with dependent variable. Data samples for this study is 350 companies listed in Indonesia Stock Exchange in 2010.The results indicate that the size of audit firms which is audited the company does influence the shares traded. The size of audit firms uses t-test. Auditor opinion, audit contract, and auditor specialization not make difference significantly to the shares traded. These variables use ANOVA. The importance of auditor opinion indicates the needed of the investor to do more research about company before invest to the company and for company to publish more company profile for external user.